A CASE OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENT WITH JACCOUD ARTHRITIS AND ALGORITHM OF ATHROPATHY IN SYSTEMIC LUPUS ERYTHEMATOSUS - Erhan Çapkın; Murat Karakucak; Mehmet Tosun; Mustafa Güler (Archives of Rheumatology, 2005)
Arthralgias or arthritis constitute the most common presenting manifestation of Systemic Lupus Erythematosus (SLE). The acute arthritis affect typically the small joint of the hands, wirsts and knees. The arthritis of SLE is typically non erosive. This condition has been called Jaccoud’s arthritis. We have presented a SLE patient with Jaccoud’s arthropathy and an arthropathy algorithm for SLE in this article.